Ethical Considerations of Preclinical Testing - Allen Goldenthal (International Association of Physical Chemists (IAPC), 2015)
The numbers of animal tests being conducted are on a sharp incline.  Much of this increase is directly due to our ability to generate transgenic models and knock-outs, thereby increasing the validity of the animal model but not necessarily correlating directly with any translational medical benefits to the human counterpart.  In spite of our best efforts, there still exist species differences that prevent the application directly from animal to human, and in some examples having a completely different and adverse effect from that seen in the animal model. There are several ways in which we can improve the opportunity for a positive test outcome and at the same time reduce the animal usage which is associated with our current animal testing practices. The benefit of the 3R's is that they encourage us not only to avoid wastage of life but that they require us to provide considerable foresight and extrapolated thought before directly engaging in the preclinical testing phase.